Generation of an induced pluripotent stem cell lines HMSCASTi001-A from peripheral blood mononuclear cells of a 35-year-old healthy male - Zhanchi Zhang; Jingrui Liu; Jiamin Zhang; Xian Xian; Peipei Hao; Yingtong Zhai; Jingke Cheng; Fengming Yue; Feng Luan; Min Ma; Qian Ren (Stem Cell Research, 2022)
Peripheral blood mononuclear cells derived from a 35-year-old healthy male were reprogrammed into induced pluripotent stem cells (iPSCs). The iPSCs maintained a normal karyotype, expressed various pluripotency stem cell markers, and showed potential of differentiating into three germ layers. This iPSCs could be differentiated into multiple cell subtypes for drug discovery and investigation of mechanisms.